A cross sectional survey of side effects of antiretroviral (ARV) in outpatients HIV by Naranjo Algorithm - Oki Nugraha Putra (Jurnal Ilmiah Farmasi, 2021)
Background: The main modality in HIV patients is the administration of long-treatment antiretroviral therapy (ARV). One of the problems from the use of ARV therapy is the side effects that can reduce patient compliance in taking medication, which has the potential to cause treatment failure.Objective: This study aims to examine the side effects and their causality in the use of ARVs in outpatient HIV patients at the VCT Clinic, Bhayangkara H.S. Hospital. Samsoeri Mertojoso Surabaya.Methods: This research was a prospective observational study with a cross-sectional design. Side effect data were taken from HIV patients by interview using the Naranjo algorithm. HIV patients who met the inclusion criteria were included in the study sample using consecutive sampling. This research was conducted from January to March 2020.Results: There were 72 outpatient HIV patients who met the inclusion criteria. The most opportunistic infections found in HIV patients are tuberculosis and Pneumocystis pneumonia. The results showed that the most common side effects experienced by patients were dizziness (43%), nausea and vomiting (31%), and rash (11%) with the highest Naranjo score being in the probable category of 86%. The Naranjo score in HIV patients with opportunistic infections and with comorbidities was significantly smaller than those in HIV patients without opportunistic infections or without comorbidities with independent t-test (P <0.05).Conclusion: The side effects in HIV patients while undergoing treatment with antiretroviral therapy are classified as a minor side effect and the cause of the side effects that occur is thought to be due to the probable category of ARV therapy.Keywords: HIV Patients, Antiretroviral, Side Effects, Naranjo's Algorithm.IntisariPendahuluan: Modalitas utama pada pasien HIV ialah pemberian terapi antiretroviral (ARV) dalam jangka waktu yang panjang. Salah satu masalah yang timbul dari penggunaan terapi ARV ialah efek samping obat yang dapat menurunkan kepatuhan pasien dalam minum obat sehingga berpotensi menimbulkan gagal pengobatan.Tujuan: Penelitian ini bertujuan untuk mengkaji efek samping dan kausalitasnya pada penggunaan ARV pada pasien HIV rawat jalan di Poli VCT, Rumah Sakit Bhayangkara H.S. Samsoeri Mertojoso Surabaya.Metode: Penelitian ini merupakan penelitian observasional prospektif dengan desain penelitian cross-sectional. Data efek samping diambil dari pasien HIV dengan wawancara menggunakan algoritma naranjo. Pasien HIV yang memenuhi kriteria inklusi dimasukkan sebagai sampel penelitian menggunakan jenis consecutive sampling. Penelitian ini dilakukan pada bulan Januari hingga Maret 2020. Hasil: Didapatkan 72 pasien HIV rawat jalan yang memenuhi kriteria inklusi. Infeksi oportunistik terbanyak yang ditemukan pada pasien HIV ialah tuberkulosis dan Pneumocystis pneumonia. Hasil penelitian menunjukan kejadian efek samping yang paling banyak dialami pasien adalah pusing (43%), mual dan muntah (31%), ruam (11%) dengan skor Naranjo terbanyak berada pada kategori probable sebesar 86%. Hasil skor Naranjo pada pasien HIV dengan infeksi oportunistik maupun dengan penyakit penyerta lebih kecil secara signifikan dibandingkan dengan pasien HIV tanpa infeksi oportunistik maupun tanpa penyakit komorbid dengan independent t-test (P<0,05).Kesimpulan: Efek samping yang ditemukan pada pasien HIV selama menjalani pengobatan dengan obat antiretroviral merupakan jenis efek samping minor dan penyebab efek samping yang terjadi diduga diakibatkan oleh obat ARV dalam kategori probable.Kata kunci:Pasien HIV, antiretroviral, efek samping, algoritma Naranjo.